The library and you: Support for postgraduate students - Selematsela, Daisy; Matizirofa, Lazarus Gallant; Tshikotshi, Aaron (University of the Witwatersrand, Johannesburg, 2025)
Postgraduate library orientations are designed to help you get familiar with the library's resources, services, and spaces.
This presentation was presented by Wits libraries, for the Postgraduate Orientation, 5 February 2025, University of the Witwatersrand, Johannesburg, 2025
Keywords: Library services; Research commons; Workshops and trainings; Online resources; Support services; Wits libraries; University of the Witwatersrand; Johannesburg; Postgraduate students orientationon; Library resources; Library facilities; SDG-4: Quality education